Rhetorical Chemistry : Negotiating Gendered Audiences in Nineteenth-Century Nutrition Studies - Lippincott, Gail (Journal of Business and Technical Communication, 2003)
This article employs neoclassic and feminist rhetorical perspectives to investigate the persuasive strategies in two scientific articles written in the late nineteenth century by Ellen Swallow Richards. One of the first credentialed female scientists in the United States, Richards wrote about nutrition research she conducted in her experimental food laboratory, the New England Kitchen, to persuade two separate audiences—one predominantly male and the other predominantly female—of the scientific value of nutrition studies. The article adds complexity to our historical underpinnings by querying how gender—of the writer, of the audiences, and in the nature of the topic—contributed to the writer’s rhetorical burdens and provides evidence that women historically have been active knowers and users of science and technology.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xMDUwNjUxOTAyMjM4NTQ0